The Paths of the Celestial Bodies According to Anaximenes - Couprie, Dirk L. (Hyperboreus, 2015)
Anaximenes is said to have maintained that the celestial bodies do not go underneath the earth, but move laterally around it like a kind of felt cap around our head. In the ﬁrst part of this article the interpretations of McKirahan and Bicknell are discussed and a new interpretation is proposed. McKirahan’s interpretation is shown to suffer from several shortcomings, such as not to account for the stars in the southern part of the heavens. Bicknell’s interpretation presupposes that Anaximenes taught a dip of the earth as is reported of Leucippus and Democritus. It is argued that this interpretation is wrong, mainly because there did not exist such a thing as a Presocratic theory of a dip of the earth: Leucippus and Democritus taught a tilt of the heavens, just like other Presocratics. Following a suggestion of Wöhrle’s, it is argued that what Anaximenes meant to describe was not the actual state of celestial affairs but that before the tilt of the heavens. In the second half of the article some methodological premises about the interpretation of ancient cosmological texts are exposed and the conclusion is drawn that Anaximenes taught not a hemispherical but a spherical universe.